Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.5 - Multiplying Polynomials - Exercise Set: 52

Answer

$x^{4}-8x^{2}+16$

Work Step by Step

$(x^{2}-4)^{2}=(x^{2}-4)(x^{2}-4)=x^{2}(x^{2}-4)-4(x^{2}-4)=(x^{2})(x^{2})+(x^{2})(-4)-4(x^{2})-4(-4)=x^{2+2}-4x^{2}-4x^{2}+16=x^{4}-8x^{2}+16$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.